Why first aid knowledge is Important - Ahmad Mohammed Al Bargi,; Sami Mansour Al Zahrani,; Hussain Mohammed Al Yami,; Muhammed Mubti Al Qahtani,; Fayes Masfer Lasloom, (International Journal of Medical Toxicology and Legal Medicine, 2025)
First aid is a fundamentally important resource for people and may mean the difference between life and death in emergencies; however, awareness and training are still lacking in many parts of the world. This paper outlines why first aid knowledge is necessary for everybody, no matter your profession or age, and is based on several recent studies from diverse populations of people, including students, teachers, and family caregivers, to cover the gaps in awareness, the benefits of early training, and evidence of educational interventions. It stresses the importance of educating people in first aid; first aid education can help empower an individual to act in a crisis, and also contribute to safer communities by enabling preparedness and resilience. The paper reviews global research in first aid education and discusses the importance of knowledge retention, attitude change, and real-life response behaviours that were identified as an impact of taking first aid training. Additionally, the paper describes a number of systemic barriers to first aid education, including institutional support and public awareness. The paper concludes by recommending free, accessible first aid training for everybody as a public health imperative.